Black men, mean streets (AMS International, 1991)
Summary: Black men, mean streets depicts the plight of the young black male in American society. This video report concentrates on the scope of the problem of a segment of the population that has consistently remained at the socio-economic bottom of an advanced society. The content of this program fits the curricula of U.S. History, Black Studies, Sociology, and Psychology courses. Activities and discussion focus on critial thinking and problem solving on a whole class, individual, and small group level.